2010
DOI: 10.1590/s1413-80502010000200004
|View full text |Cite
|
Sign up to set email alerts
|

The perception of corruption in a cross-country perspective: why are some individuals more perceptive than others?

Abstract: We examine the foundations of corruption perception at the microlevel. Using micro and macro data, we focus on the incidence of personal characteristics and country effects. We extend previous researches by estimating sub-models taking into account differences in the countries of residence. Our database comes from the 2004 International Social Survey Program survey that includes more than 35 countries. Ordered probit models were estimated in order to study the impact of independent variables on the perceived l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
24
1
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 22 publications
2
24
1
4
Order By: Relevance
“…These results reinforce the position of Melgar et al (2010) and Enstrin et al (2013) that corruption can be an inhibitor to entrepreneurial intention. Also, our results agree with the general idea according whom Italian students are limited in their work choices by "external variables".…”
Section: H5supporting
confidence: 89%
See 2 more Smart Citations
“…These results reinforce the position of Melgar et al (2010) and Enstrin et al (2013) that corruption can be an inhibitor to entrepreneurial intention. Also, our results agree with the general idea according whom Italian students are limited in their work choices by "external variables".…”
Section: H5supporting
confidence: 89%
“…What should be noted is that, despite these different definitions, there is an overwhelming consensus in the literature of the disruptive power that corruption has over economic systems. According to Melgar et al (2010), corruption perception is cultural phenomena that depends on a deviation from the social understanding of the rules. Indeed, it depends on personal and moral values and reflects the propensity of people to pay in order to receive something illegal.…”
Section: Corruption Perceptionmentioning
confidence: 99%
See 1 more Smart Citation
“…This finding is reported by Melgar, Rossi, Smith (2010). Next subchapter describes the methodology of the research.…”
Section: Area Of Livingmentioning
confidence: 91%
“…This macro-level approach has provided a breadth of valuable information and understanding about corruption, and now research is moving toward understanding the micro-level determinants of corruption. Considerable research has examined the roles that gender, age, and educational levels have on permissiveness (Hofstede, 2001;Lavena, 2013;Melgar, Rossi, & Smith, 2010;, and has determined that different characteristics and backgrounds can significantly influence individuals' condonation or acceptance of corruption. Mishler and Rose (2008) found that individuals' experiences tended to influence their perceptions of corruption.…”
mentioning
confidence: 99%